A PERUMDAM TIRTA KERTA RAHARJA PERFORMANCE EVALUATION IN THE PROVISION SYSTEM DRINKING WATER SERVICE WITH BALANCED SCORECARD, DELPHI, EIGEN VECTOR: EVALUASI KINERJA PERUMDAM TIRTA KERTA RAHARJA DALAM SISTEM PENYEDIAAN PELAYANAN AIR MINUM DENGAN BALANCED SCORECARD, DELPHI, EIGEN VEKTOR - M Rachman Waluyo; Nanang Alamsyah; Riyanda Diyosi Agista Agis (Journal of Optimization System and Ergonomy Implementation, 2024)
The availability of clean water is a serious challenge population growth and demand for drinking water increase. More than 2 billion people experience water crises every year days, projections towards 2050 predict a supply shortage clean water for one in four individuals. In Indonesia, with population of 230 million, PERUMDAM, which manages the water system taps, experiencing performance limitations and financial constraints. Evaluation using the Balanced Scorecard at PERUMDAM Tangerang Regency TKR aims to improve water services by identifying weaknesses, providing performance assessment, and provide recommendations for improvement.